2023
DOI: 10.1097/pq9.0000000000000655
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Clinical Decision Support in the Treatment of Urinary Tract Infection across a Large Pediatric Primary Care Network

Abstract: Introduction: Cystitis and pyelonephritis are common bacterial infections in infants and children, and initial treatment is usually empirical. Antimicrobial stewardship advocates using narrow-spectrum antibiotics with consideration for local resistance patterns. Narrow-spectrum antibiotic use is critical in addressing the global issue of bacterial antimicrobial resistance, associated with approximately 5 million annual deaths. Methods: The antimicrobial stewardship committee developed a guideline for diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This primary care network has done similar work in the past. 26,27 Eversole demonstrated success using similar tools on a small scale in a single Adolescent Medicine clinic. 28 Harder et al 29 described the use of a learning collaborative composed of seventeen nonintegrated practices in Vermont to increase depression screening in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This primary care network has done similar work in the past. 26,27 Eversole demonstrated success using similar tools on a small scale in a single Adolescent Medicine clinic. 28 Harder et al 29 described the use of a learning collaborative composed of seventeen nonintegrated practices in Vermont to increase depression screening in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that a suite of similar interventions can improve other domains of primary care screening and clinical management. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that a suite of similar interventions can improve other domains of primary care screening and clinical management. 13,14 We expected that improved adherence to laboratory screening recommendations for patients with obesity might have had a secondary outcome of increasing referrals to subspecialties, including endocrinology, cardiology, gastroenterology, and obesity medicine. This was not the case, however.…”
Section: Discussionmentioning
confidence: 99%